Advances in chemical stratigraphy of Pimenteiras Formation, devonian of Parnaíba Basin, Brazil. (October 2022) - Martins, Loren Pinto; Brito, Marco; Portela, Helena Antunes; Rodrigues, René; Bergamaschi, Sérgio; Chaves, Hernani Aquino Fernandes; Jones, Cleveland Maximino
Abstract: The oil potential of the Brazilian Paleozoic basins is related to conventional hydrocarbon and unconventional and atypical processes. The Parnaíba Basin fits into the atypical model. Located in Northeast Brazil, it covers approximately 600, 000 km 2 and includes different sedimentation cycles, from the Precambrian to the Mesozoic. This work seeks to reduce exploratory uncertainties in this basin by using organic geochemistry on samples from shallow wells located on the basin's eastern edge to identify and track key surfaces in the Devonian section. The intervals with total organic carbon (TOC) content above 0.5% were subjected to Rock-Eval pyrolysis analyses, while organic carbon isotope analyses (δ 1 ³C), liquid chromatography, and gas chromatography coupled with mass spectrometry (GC-MS) were performed on the intervals previously identified as being necessary for the generation of oil and gas. Detailed stratigraphic analysis of the Pimenteiras Fm from shallow wells drilled on the basin's eastern edge allowed the identification of two main marine flooding surfaces of Eifelian and Givetian age (surfaces A and B), which limit a third-order genetic sequence (AB). The association of TOC, pyrolysis, δ 1 ³C, biomarkers, and palynofacies data allowed the subdivision of the same section into four chemostratigraphic units, named L-I to L-IV, from the base to the top, and the subdivision of the section on the southwestern edge into three units, named SO–I to SO-III, from the base to the top of outcrop A. The main flooding events in the basin's eastern edge are at the base of unit L-I and unit L-IV and coincide with surfaces A and B, mapped on the gamma-ray logs that limit sequence AB. On the southwestern edge, unit SO-III represents the main flooding event. This new information improves the knowledge regarding the stratigraphy, paleoenvironment, and types of organic matter of the Pimenteiras Fm. Highlights: Organic carbon isotopes and Devonian biomarkers are studied. The Devonian paleoceanographic events are identified in Parnaíba Basin. Stratigraphic landmarks are created for Devonian marine flood events.